2022
DOI: 10.1177/15598276221092971
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the “Joy of Healthy Eating” to Advanced Medical Students: Utilizing a Remote Learning Platform to Teach Culinary Medicine: Findings from the First Online Course Based on the ACLM’s Whole-Food Plant-Based Culinary Medicine Curriculum

Abstract: Over 80% of chronic disease is caused by lifestyle practices, including an unhealthy diet. Despite this, most medical students in the United States graduate having received minimal nutrition education, guidance towards improving their nutrition, or skills needed to coach patients to adopt a healthier diet. This study aimed to educate fourth-year medical students in evidence-based knowledge regarding a delicious, whole-food plant-based diet while introducing practical culinary skills and patient coaching skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…In 2022, 14 new publications evaluated the viability of using CMC in medical/nutritional education. 13 , 21 , 41 , 50 52 Studies have also evaluated knowledge and confidence in counselling. 31 , 35 …”
Section: Discussion and Recommendations For Future Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2022, 14 new publications evaluated the viability of using CMC in medical/nutritional education. 13 , 21 , 41 , 50 52 Studies have also evaluated knowledge and confidence in counselling. 31 , 35 …”
Section: Discussion and Recommendations For Future Studiesmentioning
confidence: 99%
“…Of 47, 29 articles were published during this period. Researchers advanced the CM knowledge base by studying the impact of CM education, 50 , 51 , 59 barriers to implementing CMC, 48 , 60 remote learning of CM, 41 , 47 , 52 and the impact of CM training on patients’ health. 61 Our findings also revealed that most of these studies had been published over the last five years.…”
Section: Discussion and Recommendations For Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CMC continues to be offered and has been utilized in the form of a teaching kitchen elective course for medical and physician assistant students at Stanford University School of Medicine and showed significant improvements in attitudes, knowledge, and behaviors around healthy cooking and meal planning (4). Other studies on CM educational programs for health care professionals in training have demonstrated significant and positive impacts on medical students' attitudes, knowledge, and competencies with practical, hands-on culinary skills and nutrition knowledge (12,(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…While culinary medicine classes are traditionally taught in-person in a kitchen setting, virtual adaptations of culinary medicine have been successfully delivered in medical schools, with evidence of feasibility and a comparable impact to in-person classes [12][13][14]. We piloted a remotely delivered culinary medicine course for the GI fellowship training program at the University of California, Irvine (UCI).…”
Section: Introductionmentioning
confidence: 99%